The relationship between balance and flu-like symptoms: A medical condition that needs attention (Annals of Medical Research, 2023)
Aim: In general, while upper respiratory tract viruses cause flu-like complaints, balance problems associated with these viruses are often overlooked. It has been a long time since the first appearance of COVID-19, but unfortunately, there is still no fully effective treatment for this disease. Along with balance manifestations, especially several vestibular symptoms such as dizziness, vertigo, and tinnitus are described as common clinical manifestations in COVID-19. In our study, we investigated the effects of COVID-19 on the balance system with routine balance tests and we tried to localize a possible disorder in the balance system.Materials and Methods: Volunteers were divided into two groups. The number of volunteers in each group was thirty. The first group consisted of SARS-CoV-2-positive patients and the second group consisted of healthy people. Spontaneous nystagmus determination, Romberg test, Fukuda stepping test (FST), head thrust test (HTT), head shake test (HST), finger-nose test, and tandem walking test were applied.Results: The lateral fall in the Romberg test, rotation in the FST, and nystagmus in the HST are significant in Group 1 (p
Keywords: Vertigo; Saccades; Dizziness; Saccule and utricle